2010
DOI: 10.1111/j.1471-4159.2009.06509.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol induction of steroidogenesis in rat adrenal and brain is dependent upon pituitary ACTH release and de novo adrenal StAR synthesis

Abstract: J. Neurochem. (2010) 112, 784–796. Abstract The mechanisms of ethanol actions that produce its behavioral sequelae involve the synthesis of potent GABAergic neuroactive steroids, specifically the GABAergic metabolites of progesterone, (3α,5α)‐3‐hydroxypregnan‐20‐one (3α,5α‐THP), and deoxycorticosterone, (3α,5α)‐3,21‐dihydroxypregnan‐20‐one. We investigated the mechanisms that underlie the effect of ethanol on adrenal steroidogenesis. We found that ethanol effects on plasma pregnenolone, progesterone, 3α,5α‐THP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 64 publications
3
49
1
1
Order By: Relevance
“…Therefore, ethanol-induced changes in cellular 3a,5a-THP are bidirectional, brain region/cell population-specific, and occur locally in the rat brain. The current IHC results and previous reports using RIA or GC-MS suggest ethanol-induced elevations of 3a,5a-THP in the cerebral cortex are dependent on the adrenal or pituitary glands (Boyd et al, 2010). It is not clear why there is a dependence on the HPA axis to observe cerebral cortical elevations of 3a,5a-THP; however, one possibility is a lack of precursor in the cortex.…”
Section: Discussioncontrasting
confidence: 38%
See 3 more Smart Citations
“…Therefore, ethanol-induced changes in cellular 3a,5a-THP are bidirectional, brain region/cell population-specific, and occur locally in the rat brain. The current IHC results and previous reports using RIA or GC-MS suggest ethanol-induced elevations of 3a,5a-THP in the cerebral cortex are dependent on the adrenal or pituitary glands (Boyd et al, 2010). It is not clear why there is a dependence on the HPA axis to observe cerebral cortical elevations of 3a,5a-THP; however, one possibility is a lack of precursor in the cortex.…”
Section: Discussioncontrasting
confidence: 38%
“…Indeed, it has been shown that administration of 5a-dihydroprogesterone (5a-DHP), the immediate precursor of 3a,5a-THP, restores ethanol-induced increases of 3a,5a-THP in the cerebral cortex (Khisti et al, 2003). It has also been shown that de novo adrenal synthesis of the cholesterol transporter StAR is necessary for ethanol-induced increases of 3a,5a-THP in the cerebral cortex (Boyd et al, 2010). StAR transports cholesterol to the inner mitochondrial membrane where it is converted to pregnenolone by cytochrome P450 side chain cleavage (P450scc).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, THDOC and THP (Fig. 3) have GABA A receptor-positive modulatory effects and produce inhibitory neurobehavioural effects, including anxiolytic, anticonvulsant and sedative actions (Biggio et al 2007, Morrow 2007, and may mediate some of the actions of ethanol (Biggio et al 2007, Boyd et al 2010, Kaufman et al 2010. THDOC and allopregnanolone also have actions on the hypothalamus pituitary-adrenal axis and thereby on the effects of stress (Girdler & Klatzkin 2007).…”
Section: Other Actions and Doc In Other Speciesmentioning
confidence: 99%